Respuesta :

Answer:

(a)

[tex]T_n = 3(-4)^{n-1}[/tex]

(b)

[tex]\sum\limits^n_1 { 3(-4)^{n-1}[/tex]

Step-by-step explanation:

Given

The above sequence

Solving (a): The explicit formula

The given sequence is a geometric sequence because the common ratio (r) is:

[tex]r = \frac{-12}{3} = \frac{48}{-12} = \frac{-192}{48} = \frac{768}{-192}[/tex]

[tex]r = -4[/tex]

The explicit formula is calculated using the n term of an GP.

[tex]T_n = ar^{n-1}[/tex]

[tex]T_n = 3 * (-4)^{n-1}[/tex]

[tex]T_n = 3(-4)^{n-1}[/tex]

Solving (b): Summation notation.

This implies that the sum of the sequence.

To do this, we write Tn inside the summation sign

i.e.

[tex]\sum\limits^n_1 {T_n}[/tex]

Substitute values for Tn

[tex]\sum\limits^n_1 { 3(-4)^{n-1}[/tex]

ACCESS MORE